2018
DOI: 10.1101/lm.047811.118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticosterone on mild auditory fear conditioning and extinction; role of sex and training paradigm

Abstract: Multiple lines of evidence suggest that glucocorticoid hormones enhance memory consolidation of fearful events. However, most of these studies involve male individuals. Since anxiety, fear, and fear-associated disorders present differently in male and female subjects we investigated in mice whether male and female mice perform differently in a mild, auditory fear conditioning task and tested the modulatory role of glucocorticoid hormones. Using an auditory fear conditioning paradigm with different footshock in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 66 publications
0
10
1
Order By: Relevance
“…Selectively suppressing this neuronal ensemble restores memory specificity. Given that stress-related disorders are often sexdependent and that glucocorticoids regulate fear memory formation in a sex-dependent manner (22), further investigation is warranted regarding the role of these hormones on memory generalization in females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selectively suppressing this neuronal ensemble restores memory specificity. Given that stress-related disorders are often sexdependent and that glucocorticoids regulate fear memory formation in a sex-dependent manner (22), further investigation is warranted regarding the role of these hormones on memory generalization in females.…”
Section: Discussionmentioning
confidence: 99%
“…Fear training involved placing mice into a conditioning chamber, and, 3 min later, presenting three co-terminating presentations of a tone conditioned stimulus (CS) (30s, 20.8 kHz, 82 dB) and a foot shock unconditioned stimulus (US) (2s, 0.2 mA). This mild conditioning paradigm was selected to avoid potential ceiling effects on behavior after corticosterone injections (22,23). During testing mice were place in the same (context A) and/or a novel context (context B) and freezing was assessed.…”
Section: Fear Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in response to high-dose injections of corticosterone, eyeblink conditioning acquisition was facilitated in male Long-Evans rats, but there was no impact on acquisition in female rats (Wentworth-Eidsaune, Hennessy, and Claflin 2016). Corticosterone treatment also enhanced learning in male rats on an auditory fear conditioning task, but impaired learning in female rats (Lesuis et al 2018). These sexually dimorphic behavioral responses to stress suggest that stress may underlie the behavioral differences initially observed in chronically implanted animals.…”
mentioning
confidence: 91%
“…(iii) In relation to anxiety, Oksztel et al (2002) found that systemic administration of muscimol in rats causes a general decrease in motility but has no effect on anxiety levels. And in terms of stress, previous studies (Brinks et al, 2009;Uwaya et al, 2016;Pietersen et al, 2016;Lesuis et al, 2018) have reported a correlation between the amount of freezing and corticosterone levels. Given that the amount of conditioned freezing behaviour was unaffected in our experiments, this suggests that stress is also unlikely to fully explain our findings.…”
Section: Methodological Considerationsmentioning
confidence: 93%